Promoting Green Pesantren: Change, Challenge and Contribution of Nahdlatul Ulama in Indonesia - Maghfiroh, Muliatul; Iryani, Eva; Haerudin, Haerudin; Yani, Muhammad Turhan; Zaini, Nur; Mahfud, Choirul (Nazhruna: Jurnal Pendidikan Islam, 2024)
This qualitative research elaborates that Nahdlatul Ulama (NU) is Indonesia's most prominent Islamic organization, contributing to the green pesantren. This article also explores NU's change, challenge, and contribution through Pesantren in environmental and ecological issues. The primary data in this research methodology are interviews and documents. The secondary data includes other resources that are relevant to this research, such as articles, books, and news. This research shows that NU, through the Green Pesantren program, is trying to contribute to being part of the problem solver on environmental, ecological, and climate change issues. This article also explains green pesantren as an answer to the debate about the relationship between Islam, ecology, and the environment. The concern of green pesantrenis is not only in the teaching and learning aspects of Islamic doctrine and individual piety but also in today's environmental, ecological, and human problems. In this context, the roles and functions of kiai, pesantren students, and alums in addressing environmental and ecological issues are multifaceted. They combine education, community engagement, religious perspectives, advocacy, practical solutions, and role modeling to effect meaningful change and contribute to a more sustainable future.